Evaluation of Children Undergoing Endoscopic Procedures During the Normalization of the Coronavirus Disease 2019 Pandemic - Şenay Onbaşı Karabağ; Maşallah Baran; Betül Aksoy; Yeliz Cağan Appak; Sinem Kahveci Çelik; Selen Güler; Dilek Yılmaz Çiftdoğan (Turkish Journal of Gastroenterology, 2022)
Background: Given that procedures involving gastrointestinal tract lumens are high-risk and aerosol forming, the functioning of endos- copy units has been reorganized during the coronavirus disease 2019 pandemic. Guidelines recommend that all personnel should carry out procedures in a negative-pressure room with personal protective equipment; in the absence of a negative-pressure room, an ade- quately ventilated room should be used. During the normalization of the coronavirus disease 2019 pandemic, this study aimed to evalu- ate children who were treated in our endoscopy unit without a negative-pressure chamber in terms of coronavirus disease 2019 after procedures. Methods: Patients were questioned and evaluated prospectively for symptoms and contact with coronavirus disease 2019 patients on before and 7th and 14th days after the procedure. Results: Seventy-eight procedures were performed on 69 patients over a 3-month period. The mean age of patients was 12.0 ± 5.1 years. Among all the procedures performed, 54 (69.2%) involved upper gastrointestinal system (GIS) endoscopy and 24 (30.8%) involved colo- noscopy. Furthermore, 72 (91.3%) of the procedures were performed in the pediatric endoscopy unit, and 6 (7.7%) were performed in the operating room. No coronavirus disease 2019 symptoms or presence was detected in the patients. Conclusion: The ideal setting for an endoscopic procedure is in a negative-pressure chamber. However, this study has shown that endoscopic procedures can be performed in units without negative-pressure rooms but with appropriate protective equipment and evaluation of patients for coronavirus disease 2019 symptoms. Cite this article as: Onbaşı Karabağ S, Baran M, Aksoy B, et al. Evaluation of children undergoing endoscopic procedures during the normalization of the coronavirus disease 2019 pandemic. Turk J Gastroenterol. 2022;33(6):515-519.